Cadaveric Evaluation of Injectate Distribution for Two Maxillary Nerve Block Techniques in Cats - Davis, Lily V.; Hoyer, Naomi K.; Boscan, Pedro; Rao, Sangeeta; Rawlinson, Jennifer E. (Frontiers in Veterinary Science, 2021)
Regional nerve blocks have been shown to decrease general anesthetic drug requirements and improve pain management in patients undergoing surgery. Regional nerve blocks are used routinely in patients undergoing oral surgery, such as dental extractions. There is little published information regarding the efficacy of feline maxillary and infraorbital nerve blocks. The goal of the study was to com-pare injectate distributions of the infraorbital foramen and percutaneous maxillary nerve block techniques in feline cadavers using a combined dye and radiopaque contrast media solution to simulate an injection. There was no significant difference in length of stained nerve between the two different techniques. It was not necessary to advance the needle into the infraorbital canal in order to achieve effective staining of the maxillary nerve. There was no significant difference in injectate distribution between two different injectate volumes, 0.2 ml and 0.4 ml, indicating that the smaller volume injected at the infraorbital foramen resulted in adequate nerve staining.